A detailed experimental analysis of air–steam gasification in a dual fired downdraft biomass gasifier enabling hydrogen enrichment in the producer gas. (15th November 2019) - Ram, Narasimhan Kodanda; Singh, Nameirakpam Rajesh; Raman, Perumal; Kumar, Atul; Kaushal, Priyanka
Abstract: The use of ambient air as an oxidizing agent in the biomass gasification process is well understood. Ambient air contains 79% nitrogen (N2 ) and 21% Oxygen (O2 ) by volume. Consequently, producer gas generated through air gasification comprises of non-combustible gases around 62% (on a volume basis). As a result, the heating value of the producer gas is low, which results in low adiabatic flame temperature (AFT), low AFT results in reduced efficiency and higher specific fuel consumption (SFC) when the producer gas (PG) is used in internal combustion (IC) engines. This study is focused on the reduction of the non-combustible fraction in producer gas, thereby to increase the heating value of the producer gas through the air- steam gasification. The results of the experimental study are presented in details. A detailed mass and energy balance analysis conducted. A maximum of 27.24% (by volume) hydrogen achieved at equivalence number (EN) 1.54 suitable for bio-hydrogen production. Whereas EN 1.5–2.2 is more suitable for power generation applications since maximum higher heating value (HHV) occurs in this range, i.e., 6.33 MJ Nm −3 . The enrichment of producer gas resulted in an increase of HHV by 44%. The cold gas efficiency is 86–87%. Highlights: The influential parameters of air-steam gasification were identified and optimized. The optimum range for the enrichment of the combustible fraction is when equivalence number is from 1.5–2.2 Combustible fraction increased to 43%, resulting non-combustible fraction as 57%. Due to hydrogen enrichment, the calorific value of the producer gas was increased by 44%. The maximum gas yield was 2.85 Nm 3 kg −1 with a calorific value of 6.31 MJ Nm −3 and adiabatic flame temperature 2090 K.